Clinical Value of Detecting Fecal Calprotectin by Using Colloidal Gold Assay in Screening or Diagnosing Crohn’s Disease - Wangdong Zhang; Yanyun Fan; Meijun Chen (Gastroenterology Research and Practice)
Background. Crohn’s disease (CD) is a chronic inflammatory disease, and its incidence is gradually increasing. Thus, the use of a simple and convenient examination method to detect CD in the natural population as early as possible is crucial. This study is aimed at using the colloidal gold semiquantitative assay to detect fecal calprotectin (FCP) and determine whether it is helpful in screening or diagnosing CD. Methods. Using a prospectively maintained database, 59 patients with CD were analyzed using FCP measurement. Subsequently, 76 patients and 89 healthy individuals were assigned to the gastrointestinal dysfunction and control groups, respectively. To aid in the screening or diagnosis of CD, the receiver operating characteristic curve was used to determine the diagnostic efficacy of FCP thresholds. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were presented with 95% confidence intervals (CIs). Results. Patients with CD showed significantly higher FCP levels. Compared with the healthy population, when the FCP level cut-off was 15 μg/g and 60 μg/g, the sensitivity, specificity, PPV, and NPV for CD diagnosis were 98.3% (CI, 95.0%–100%) and 78.0% (CI, 67.4–88.6%), 84.3% (CI, 76.7%–91.8%) and 98.9% (CI, 96.7%–100%), 80.6% (CI, 71.5%–89.7%) and 97.9% (CI, 93.7%–100%), and 98.7% (CI, 96.2%–100%) and 87.1% (CI, 80.6%–93.6%), respectively. The AUCs were 0.969 (CI, 0.941–0.997). Compared with the gastrointestinal dysfunction group, using the same FCP level cut-off, the sensitivity, specificity, PPV, and NPV for CD diagnosis were 98.3% (CI, 95.0%–100%) and 78.0% (CI, 67.4%–88.6%), 71.1% (CI, 60.9%–81.3%) and 89.5% (CI, 82.3%–96.7%), 72.5% (CI, 62.7%–82.3%) and 85.2% (CI, 75.7%–94.7%), and 98.1% (CI, 94.5%–100%) and 84.0% (CI, 76.0%–92.0%), respectively. The AUCs were 0.908 (CI, 0.856–0.960). Conclusion. Detecting FCP by using the colloidal gold semiquantitative assay can be effective in screening and adjunct diagnosing of CD.